Adsorption of synthetic homo- and hetero-oligodeoxynucleotides onto highly oriented pyrolytic graphite: Atomic force microscopy characterization - Paquim, Ana Maria Chiorcea (2006)
DNA adsorption on electrode surfaces is of fundamental interest for the development of DNA-based biosensors. The free adsorption of 10-mer synthetic oligodeoxynucleotides (ODNs) onto highly oriented pyrolytic graphite (HOPG) surfaces was studied using Magnetic AC mode atomic force microscopy (MAC Mode AFM). The mechanism of interaction of nucleic acids with carbon electrode surfaces was elucidated, using 10-mer synthetic homo- and hetero-ODNs sequences of known base sequences, because they allow clear interpretation of the experimental data. AFM images in air revealed different adsorption patterns and degree of HOPG surface coverage for the ODNs, and correlation with the individual structure and base sequence of each ODN molecule will be presented. The results demonstrated that the hydrophobic interactions with the HOPG hydrophobic surface explain the main adsorption mechanism, although other effects such as electrostatic and Van der Waals interactions may contribute to the free adsorption process. The ODNs interacted differently with the HOPG surface, according to the ODN sequence hydrophobic characteristics, being directly depending on the molecular mass, the hydrophobic character of the individual bases and on the secondary structure of the molecule. The importance of the type of base existent at the ODN chain extremities on the adsorption process was investigated and different adsorption patterns were obtained with ODN sequences composed by the same group of bases aligned in a different order.